Assessing healthcare access using the Levesque's conceptual framework- a scoping review - Anthony Cu; Sofia Meister; Bertrand Lefebvre; Valéry Ridde (BMC, 2021)
Abstract Introduction Countries are working hard to improve access to healthcare through Universal Healthcare Coverage. To genuinely address the problems of healthcare access, we need to recognize all the dimensions and complexities of healthcare access. Levesque's Conceptual Framework of Access to Health introduced in 2013 provides an interesting and comprehensive perspective through the five dimensions of access and the five abilities of the population to access healthcare. The objectives of this paper are to identify and analyze all empirical studies that applied Levesque's conceptual framework for access to healthcare and to explore the experiences and challenges of researchers who used this framework in developing tools for assessing access. Methods A scoping review was conducted by searching through four databases, for studies citing Levesque et al. 2013 to select all empirical studies focusing on healthcare access that applied the framework. An initial 1838 documents underwent title screening, followed by abstract screening, and finally full text screening by two independent reviewers. Authors of studies identified from the scoping review were also interviewed. Results There were 31 studies identified on healthcare access using the Levesque framework either a priori, to develop assessment tool/s (11 studies), or a posteriori, to organize and analyze collected data (20 studies). From the tools used, 147 unique questions on healthcare access were collected, 91 of these explored dimensions of access while 56 were about abilities to access. Those that were designed from the patient's perspective were 73%, while 20% were for health providers, and 7% were addressed to both. Interviews from seven out of the 26 authors, showed that while there were some challenges such as instances of categorization difficulty and unequal representation of dimensions and abilities, the overall experience was positive. Conclusion Levesque's framework has been successfully used in research that explored, assessed, and measured access in various healthcare services and settings. The framework allowed researchers to comprehensively assess the complex and dynamic process of access both in the health systems and the population contexts. There is still potential room for improvement of the framework, particularly the incorporation of time-related elements of access.